FILSAFAT DALAM RANAH PERPUSTAKAAN DAN INFORMASI: PERAN DAN PENERAPANNYA - Gusnar Zain; Dian Hasfera (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2018)
Philosophy of library can be interpreted as knowledge or knowledge that learns about the nature, basis or principle of librarianship (the science and profession of librarians). Practically (in practice), library philosophy has many roles in providing alternatives to solving various problems faced by society, and provides direction, solutions, thoughts, opinions on its success, development of knowledge, fulfillment of information, decision making, work behavior of librarians, user behavior, including providing quality services. As a new foundation, analysis and design of library philosophy and information can explain and guide the purpose of compiling the librarian intellectual environment, and provide systematic treatment of the conceptions of the foundations of a librarian environment.